Pengawasan Administrasi Kurikulim Merdeka Belajar Di MAN 2 Palembang - Fitriani, Geti; Zainuri, Ahmad (Program Studi Manajemen Pendidikan Islam Fak. Ilmu Tarbiyah dan Keguruan, 2024)
The implementation of the Merdeka Curriculum in Indonesia requires effective administrative supervision to ensure its successful execution in schools. Administrative supervision plays a crucial role in directing and monitoring various activities related to curriculum management, including planning, implementation, and evaluation. This study focuses on the administrative supervision of the Merdeka Curriculum at MAN 2 Palembang, aiming to explore the effectiveness of supervision and the challenges faced during its implementation process. The approach used in this research is qualitative-descriptive, with data collection through in-depth interviews, direct observation, and document analysis. The findings indicate that although administrative supervision at MAN 2 Palembang has been carried out well, several challenges remain, such as limited resources, a lack of understanding among teachers about the new curriculum, and the need for improved supervision quality. The use of technology in supervision has proven to enhance efficiency but has not yet been fully optimized. The conclusion of this study is that strengthening training for teachers, improving supervision quality, and fostering synergy between the school and the education office can be solutions to address these challenges. The implications of this research suggest the need for more attention to the development of curriculum supervisors' capacity and the use of technology as a tool for administrative supervision of the Merdeka Curriculum.